Peran Kantor Kementerian Agama Kabupaten Aceh Utara dalam Melaksanakan Sistem Informasi dan Komputerisasi Haji Terpadu - Afriani Afriani; Saiful Bahri; Thanthawi Ishak (Asia-Pacific Journal of Public Policy, 2020)
This study aims to gain information concerning the role, obstacles, and efforts of implementing integrated Hajj information and computerization systems at the Office of the Ministry of Religion of North Aceh Regency, Indonesia. Qualitative approaches were employed in collecting the data through observations and interviews. The results revealed that the role of the Office of the Ministry of Religion of North Aceh Regency in implementing the Integrated Hajj Information and Computerization System (SISKOHAT) is still not optimal, based on the report from the society. The problem is the insufficient time to serve the pilgrims who want to register because the group must firstly receive a validation number from BPS-BPIH. The IT facilities (e.g., internet, computers) are also inadequate to support this computerization system program. Besides, the office facilities are not supported or friendly for the majority of elderly pilgrims. Another problem is the lack of sufficient information provided to the pilgrims. Based on these issues, we strongly suggest stakeholders evaluate their services regarding the Hajj information and computerization systems. In terms of information services, service contact numbers (Call Center) should be accommodated to enable the pilgrims to obtain information without wasting much effort and time revisiting the Ministry of Religion office regularly.